The Religion of the Rigveda - Oberlies, Thomas (Oxford University Press, Incorporated, 2024)
As one of the world's major religions, Hinduism has been studied from countless perspectives. What is often neglected, however, is the study of the Rigvedic religion as its ancestor. The Religion of the Rigveda uncovers fundamental concepts found in Hinduism, providing an up-to-date foundation for renewed examination of the origins of Hinduism.